2020
DOI: 10.21203/rs.3.rs-39860/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of investigational microbiota therapeutic RBX2660 on the gut microbiome and resistome revealed by a placebo-controlled clinical trial

Abstract: Background. Intestinal microbiota restoration can be achieved by complementing a subject’s perturbed microbiota with that of a healthy donor. Recurrent Clostridioides difficile infection (rCDI) is one key application of such treatment. Another emerging application of interest is reducing antibiotic resistant genes (ARGs) and organisms (AROs). In this study, we investigated fecal specimens from a multicenter, randomized, double-blind, placebo-controlled phase 2b study of microbiota-based investigational drug RB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…28 Analyses of stool specimens from the RBX2660 phase 2b double-blinded, placebo-controlled, randomized trial using metagenomic sequencing found that RBX2660 reduced ARO colonization and more rapidly restored the microbiota compared to placebo. 29 MRT administered for CDI has also been associated with reductions in urinary tract infections. 30 Notably, a detailed cased report in which RBX2660 was administered for treatment of recurrent antimicrobial-resistant Klebsiella pneumoniae UTIs suggests that decolonization may not be the mechanism by which MRT interacts with ARO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Analyses of stool specimens from the RBX2660 phase 2b double-blinded, placebo-controlled, randomized trial using metagenomic sequencing found that RBX2660 reduced ARO colonization and more rapidly restored the microbiota compared to placebo. 29 MRT administered for CDI has also been associated with reductions in urinary tract infections. 30 Notably, a detailed cased report in which RBX2660 was administered for treatment of recurrent antimicrobial-resistant Klebsiella pneumoniae UTIs suggests that decolonization may not be the mechanism by which MRT interacts with ARO.…”
Section: Discussionmentioning
confidence: 99%
“…31 Notably, potential risks are associated with MRT administration for ARO colonization, including transferring new resistant organisms or genes to the recipient. 29 Additional study is needed to better understand the mechanisms, benefits, and harms of MRT when administered for ARO colonization before adoption into clinical practice. 22 Probiotics overall are safe, but it is also important to consider the potential for organisms in probiotic formulations to cause infections, particularly in immunocompromised patients who may be at risk of gut microbiota disruption due to other factors.…”
Section: Discussionmentioning
confidence: 99%
“…These include FMT-based products derived from donor stool, such as frozen stool capsules, lyophilized microbes, bacterial consortia, or purified spores isolated from stool. 80 They have been tested for treating recurrent CDI 81,82 and other conditions 83,84 with variable successes. Other non-FMT-based approaches have been developed, such as direct strategies to enrich certain beneficial bacteria by probiotics, to deplete harmful bacteria by antibiotics, or indirect strategies to change the gut microbiota through prebiotics or personalized nutrition.…”
Section: Unknowns In Other Microbiota Therapeuticsmentioning
confidence: 99%
“…A study investigating fecal specimens from 66 recipients and the RBX2660 product in a multicenter, randomized, double-blind, placebo-controlled phase IIb study showed that RBX2660 not only shifted the taxonomic structure of the intestinal microbiome in the recipient group, but it also lead to dynamic changes in their antibiotic resistance patterns. 69 Besides decreasing the overall antibiotic resistance in the microbiome, it also simultaneously introduced RBX2660-origin antibiotic-resistant genes (ARGs) in a dose-dependent manner. This emphasizes the importance of screening fecal transplant samples for medically important ARGs via highly sensitive molecular methods.…”
Section: Serious Infection Transmission Associated With Fmtmentioning
confidence: 99%